EFFECTS OF SURFACE CONDITIONS FOR DIFFERENT CLIMATIC ZONES IN TURKEY ON TEMPERATURE DISTRIBUTION IN THE SOIL - Kayaci, Nurullah; Demir, Hakan; Atayilmaz, S. Ozgur; Agra, Ozden (AMER SOC MECHANICAL ENGINEERS, 2016)
Ground Heat Exchangers (GHEs) are an important parts of Ground Source Heat Pump (GSHP) systems and its dimensions and burial depth should be calculated using an effective method considering surface conditions. Particularly, the cost of the assembly of GHE affects the choice of these systems. For efficiency of the GSHP system, the heat extracted from or dissipated to the soil should not be changed by time for longer period runs of GSHP systems. Typical values for Coefficient of Performance (COP) of Ground Source Heat Pumps (GSHPs) are up to 8 while it is 4 of air source heat pumps. Soil composition, density, moisture and burial depth of pipes affect the size of a GHE. The burial depth and the distance between the pipes are important for sizing the GHEE. Because of the complexity of the boundary conditions, a numerical study was conducted to investigate the effects of time-dependent external weather conditions, burial depth, soil thermal properties and extracted heat from soil on temperature distribution in the soil. Heat transfer in the soil is time dependent three dimensional heat conduction with dynamical boundary conditions. The GHEs consist of pipes buried in the soil and are used for transferring heat between the soil and the heat exchanger pipes of GSHP. Numerical analysis performed in ANSYS software using a UDF for dynamical boundary conditions. In order to provide the periodic variation of air temperature boundary at upper surface condition was written a User Defined Function (UDF) and it can be interpreted in ANSYS Fluent. Likewise, a UDF was also written to give constant heat flux intermittently for the pipe inner surface. Temperature distribution in soil were obtained for different climatic zones and burial depths of 1 - 2 m. It was seen that the surface conditions of different climatic zones has great importance up to a critical value of burial depth.
Keywords: HEAT-PUMP SYSTEM; MASS-TRANSFER MODEL; BURIED PIPE; EXCHANGER; FLOW; Engineering